On Strongly Convex Functions via Caputo–Fabrizio-Type Fractional Integral and Some Applications - Qi Li; Muhammad Shoaib Saleem; Peiyu Yan; Muhammad Sajid Zahoor; Muhammad Imran (Journal of Mathematics)
The theory of convex functions plays an important role in the study of optimization problems. The fractional calculus has been found the best to model physical and engineering processes. The aim of this paper is to study some properties of strongly convex functions via the Caputo–Fabrizio fractional integral operator. In this paper, we present Hermite–Hadamard-type inequalities for strongly convex functions via the Caputo–Fabrizio fractional integral operator. Some new inequalities of strongly convex functions involving the Caputo–Fabrizio fractional integral operator are also presented. Moreover, we present some applications of the proposed inequalities to special means.